0761 Prevalence of Diagnosed Pediatric Narcolepsy in the United States. (12th April 2019) - Morse, Anne M; Licholai, Greg; Yang, Mo; Bron, Morgan; Profant, Judi; Villa, Kathleen F
Abstract: Introduction: Prevalence of pediatric narcolepsy has not been well studied. The objective was to estimate the prevalence of diagnosed narcolepsy in pediatric patients (0-17 years) in a large US healthcare claims database. Trends in diagnosed narcolepsy among pediatric patients also were assessed and extrapolated to the US pediatric population. Methods: Nationwide medical/prescription claims (Symphony Health) were utilized to assess prevalence of diagnosed narcolepsy per 100, 000 pediatric patients for each calendar year (2013-2016). Data on age (0-6, 7-11, 12-17 years), sex, insurance type, and narcolepsy type (with/without cataplexy) were collected. Cases were identified as having either ≥2 claims with a narcolepsy diagnosis (with/without cataplexy) ≤6 months apart, or ≥1 narcolepsy claim and ≥1 multiple sleep latency test or maintenance of wakefulness test within 6 months before the narcolepsy claim. Direct standardization was applied to narcolepsy prevalence to control for possible changes in the age-sex distribution of the database. Results: The majority of pediatric patients with narcolepsy in the database were aged 12-17 years (79.0%), female (51.6%), commercially insured (62.8%), and had diagnosis claims of narcolepsy without cataplexy (56.4%). Standardized pediatric narcolepsy prevalence increased from 8.9 (95% confidence interval [CI] 8.3-9.5) per 100, 000 persons in 2013 to 10.0 (95% CI 9.3-10.6) in 2016. When extrapolated to the US pediatric population, estimated prevalence of diagnosed narcolepsy increased from 6, 780 persons in 2013 to 7, 606 in 2016. Estimated diagnosed prevalence increased by age category from 0.7 per 100, 000 for 0-6 years to 6.9 for 7-11 years and 24.0 for 12-17 years. Codes for cataplexy in claims suggest a standardized prevalence of diagnosed narcolepsy with cataplexy of 2.9 per 100, 000 in 2013 and 4.4 in 2016. Conclusion: The prevalence of diagnosed pediatric narcolepsy increased over the study period. Findings likely represent an underestimate, as this database only includes diagnosed and insured patients. Further research is needed to understand the prevalence of narcolepsy among the undiagnosed/uninsured pediatric population and the challenges in identifying cataplexy in pediatric patients, given the high rate of narcolepsy without cataplexy observed in this study. Support (If Any): Jazz Pharmaceuticals